PENGARUH CAMPURAN DUA AGREGAT HALUS TERHADAP KUAT TEKAN BETON - Agustin Gunawan (Universitas Bengkulu, 2019)
Increasing Exploration of river sand push an action to find other aternative excepting river sand. Using of sea sand become alternative as fine aggregate mixed on making of concrete. The research is conducted to know the effect of fine aggregate mixed to concrete compressive strength. Two kinds of fine aggregate used are river sand (PS) from Pondok Kelapa and sea sand from Lais, which is all bad gradation. Coarse Aggregates used are from quarry Sukaraja and quarry Pondok Kubang. Sea sand consists of two conditions which is not washed (PLTC) and washed (PLC) without regard to content of its mud. Number of samples was 42 samples which were cylindrical in shape with diameter of 15 cm and height of 30 cm. The research carried out by combined 65% PS + 35% (PLC or PLTC) and 75% PS + 25% (PLC or PLTC) then compared it to concrete of comparison. Test of concrete compressive strength was performed at 28 days. The result showed that the greatest concrete compressive strength was 16,88 MPa occured on a mixture of 75% PS + 25% PLTC using coarse aggregate from Sukaraja. Mixture of 75% PS + 25% PLTC using coarse aggregate from Sukaraja increased concrete compressive strength of 5,47 MPa (+47,93%) to concrete of comparison using 100% PLTC and 4,05 MPa (+24,02%) to concrete of comparison using 100% PS.